Effect of Moral Sensitivity on Green Behavior, Green Economy and Function of Moral Identity, Moral Judgment Mechanisms: Rational Moral View - Zennouche Mohamed (Journal of Management Practices, Humanities and Social Sciences, 2024)
Today’s world, the pathway of worldwide economic development is ecologically unsustainable. The actual paradigm of production and consumption degrade and drain many of the world’s environmental resources. These have been intensified by recent energy, food, and financial crises. Continuous warning, the world economy and human well-being is in danger of transgressing several of planetary boundaries or ecological limits. There is in this way a require modern call upon governments to create national methodologies for economic improvement, consolidating arrangement measures. In spite of the endeavors of numerous governments around the world to actualize such techniques as well as international cooperation to bolster national governments, there are proceeding concerns over worldwide financial and natural improvements in numerous nations’ approaches that can advance comprehensive and ecologically economical financial improvement. Working towards a green economy offers such approaches. Countries' policy framework for international development cooperation must take into consideration the environmental policy. Additionally, it promotes broad-based employment and reduction and the decrease of poverty in all of its forms. This brief explains why the green economy is needed, what it is, how it can be done, and what employees’ green behavior does, and it can do, based on the rational view of decision-making, considering moral judgment, moral sensitivity, and moral identity. This paper identifies the mechanism influencing green behavior and green economy, started from moral sensitivity as independent variable and green behavior, green economy as dependent variables, moreover the paper clearly describe the functions of moral identity and moral judgment in this conceptual model.